Enhancing Climate Resilience through Integrative Approaches: A Synthesis of Indigenous and Scientific Knowledge Systems - Anak Kemarau Ricky; Sakawi Zaini; Anak Suab Stanley; Valentine Eboy Oliver (E3S Web of Conferences)
Indigenous Knowledge (IK) systems offer valuable insights into local environmental patterns and climatic changes, yet they remain underutilized within formal scientific frameworks. This study synthesizes findings from integrative approaches combining IK with scientific knowledge to enhance climate resilience. Utilizing a review of literature sourced from Web of Science, Scopus, and Science Direct, the paper identifies key areas where IK significantly augments scientific understanding of climate phenomena. Findings suggest that hybrid knowledge systems improve the accuracy and acceptance of climate forecasts, empowering local communities and enhancing adaptive capacities. This synthesis underscores the need for creating inclusive frameworks that respect and integrate diverse knowledge systems for sustainable climate resilience.